Saprolegnia milnae (Saprolegniales, Straminipila), a new species from an Argentine river (Tierra del Fuego Province, Argentina) - Steciow, Mónica Mirta (2002)
Saprolegnia milnae is described from litter (floating dead twigs, leaves, and roots) in the Milna River, Ushuaia Department, Tierra del Fuego Province (Argentina). The new species is illustrated and compared with other species of the genus. Distinguishing characteristics of S. milnae are the production of smooth oogonia and predominantly contorted androgynous antheridial branches, and also monoclinous and diclinous ones. The oogonial stalks are predominantly bent, curved or once coiled; oospores are subcentric, (1—)3—23(—40) per oogonium, and are variable in size, reaching a diameter of up to 60 μm.